Adaptation Pathways in Coastal Case Studies: Lessons Learned and Future Directions. Issue 5 (3rd September 2017) - Lin, Brenda B.; Capon, Tim; Langston, Art; Taylor, Bruce; Wise, Russ; Williams, Rachel; Lazarow, Neil
ABSTRACT: Climate change adaptation presents a difficult challenge for coastal towns around the world, forcing local governments to plan for sea level rise in a contentious decision-making space. The concept of "adaptation pathways, " a diagnostic and analytical tool to assist in adaptive planning and decision-making, is gaining traction as a way of framing and informing climate adaptation. It provides decisionmakers a way to acknowledge the inter-temporal complexities and uncertainties associated with the novel dynamics of climate change and a mechanism to manage these challenges in the local context. In 2012, the Australian Government funded an 18-month program to provide decisionmakers in the coastal zone an opportunity to test the utility of the adaptation pathways concept for coastal climate adaptation. Using a selection of completed projects as case studies, we performed a document analysis to better understand the learnings from the projects. The main themes surrounded: (1) the utility of the adaptation pathway framework in developing options, (2) decision-making rationale and criteria, and (3) stakeholder participation in pathway development. A project participant survey was developed to further understand these themes. Our analysis reveals that "adaptation pathways" was generally framed narrowly and conservatively to emphasize extant economic, administrative and legal considerations over community, participatory, or exploratory ones. Although some case study projects were able to reach a point in the pathway discussion to actively involve stakeholders in their decision-making process, many case studies continued to build technical data as a method for defending policies and actions. These results indicate that coastal adaptation can take-up adaptation pathways as a useful concept for decision-making and planning; however, many councils may still require assistance in stakeholder communication processes in order to develop sociallyacceptable plans that take into account the full range of values affecting local coastal environments.